Celebrity Authorship and Afterlives in English and American Literature - Honings, Rick. author. aut Link
XII, 209 p. 15 illus., 4 illus. in color.
Keywords: This book maps the history of literary celebrity from the early nineteenth century to the present, paying special attention to the authors’ crafting of their writerly self as well as the afterlife of their public image. Case studies are John Keats, Edgar Allan Poe, Eliza Cook, Herman Melville, Oscar Wilde, Gertrude Stein, J.D. Salinger and Zadie Smith. Literary celebrity is part and parcel of modern literary culture, yet it continues to raise intriguing questions about the nature of authorship, writerly fame and the tension between authorial self-fashioning and public appropriation. This volume provides unique insights into the phenomenon.